2014
DOI: 10.1021/mp400735c
|View full text |Cite
|
Sign up to set email alerts
|

Brain Uptake of a Zidovudine Prodrug after Nasal Administration of Solid Lipid Microparticles

Abstract: Our previous results demonstrated that a prodrug obtained by the conjugation of the antiretroviral drug zidovudine (AZT) with ursodeoxycholic acid (UDCA) represents a potential carrier for AZT in the central nervous system, thus possibly increasing AZT efficiency as an anti-HIV drug. Based on these results and in order to enhance AZT brain targeting, the present study focuses on solid lipid microparticles (SLMs) as a carrier system for the nasal administration of UDCA-AZT prodrug. SLMs were produced by the hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 53 publications
(125 reference statements)
4
46
0
Order By: Relevance
“…The nasal administration of pure UDCA-AZT as a water suspension did not allow us to obtain detectable amounts of AZT or the prodrug in the blood or in the CSF, respectively, within 180 min of administration, as reported previously (Dalpiaz et al, 2014). In contrast, the nasal administration of the powders constituted by MIX or by the CP microparticles (0.8 mg, 19 approximately 100 µg of UDCA−AZT in each nostril) produced detectable amounts of UDCA−AZT in the CSF of the rats, as reported in Fig.…”
Section: Nasal Administration Of Udca−aztsupporting
confidence: 58%
See 3 more Smart Citations
“…The nasal administration of pure UDCA-AZT as a water suspension did not allow us to obtain detectable amounts of AZT or the prodrug in the blood or in the CSF, respectively, within 180 min of administration, as reported previously (Dalpiaz et al, 2014). In contrast, the nasal administration of the powders constituted by MIX or by the CP microparticles (0.8 mg, 19 approximately 100 µg of UDCA−AZT in each nostril) produced detectable amounts of UDCA−AZT in the CSF of the rats, as reported in Fig.…”
Section: Nasal Administration Of Udca−aztsupporting
confidence: 58%
“…Accordingly, we demonstrated that the nasal administration of solid lipid microparticles loaded with the UDCA-AZT prodrug facilitates its uptake into the CSF of rats (Dalpiaz et al, 2014). Nasal administration constitutes a potentially efficacious way of achieving the brain uptake of neuroactive agents (Fine et al, 2014(Fine et al, , 2015Illum, 2000;Vyas et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In particular, this may provide a much higher residence time in the nasal cavity, pivotal to allow an enhancement of drug availability. 66 For the in vitro release studies, a simulated nasal electrolyte solution containing BSA was preferred to surfactant solutions 48 or mixtures with organic solvents miscible with water 67 , as a physiological dissolution medium. Generally, drug inclusion in nanoparticles is a strategy to prolong the release.…”
mentioning
confidence: 99%